2020
DOI: 10.1126/scisignal.aaz1236
|View full text |Cite
|
Sign up to set email alerts
|

Transomics analysis reveals allosteric and gene regulation axes for altered hepatic glucose-responsive metabolism in obesity

Abstract: Impaired glucose tolerance associated with obesity causes postprandial hyperglycemia and can lead to type 2 diabetes. To study the differences in liver metabolism in healthy and obese states, we constructed and analyzed transomics glucose-responsive metabolic networks with layers for metabolites, expression data for metabolic enzyme genes, transcription factors, and insulin signaling proteins from the livers of healthy and obese mice. We integrated multiomics time course data from wild-type and leptin-deficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
103
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 26 publications
(107 citation statements)
references
References 74 publications
4
103
0
Order By: Relevance
“…7 A). A recent paper published by Kokaji et al reported the transcriptomes of mice liver from ten-week-old male ob/ob mutant and C57BL/6 wild type mice [ 13 ]. The comparison of the two mice liver groups showed 6693 genes significantly regulated at a p value < 0.05 (Additional file 1 : Figure S4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 A). A recent paper published by Kokaji et al reported the transcriptomes of mice liver from ten-week-old male ob/ob mutant and C57BL/6 wild type mice [ 13 ]. The comparison of the two mice liver groups showed 6693 genes significantly regulated at a p value < 0.05 (Additional file 1 : Figure S4).…”
Section: Resultsmentioning
confidence: 99%
“…Using a positional isotopomer NMR tracer analysis method, Perry et al showed that leptin mediates a glucose-fatty acid cycle to maintain glucose homeostasis in starvation in rats [ 12 ]. Using a combination of metabolomics and transcriptomics, a recent published paper demonstrates that the carbohydrate, lipid and amino acid metabolic liver responses to glucose administration are broadly different between wild type and ob/ob mice [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, both groups reached a steady state four hours after oral glucose administration. The transcriptomic data were reported in our previous studies (Egami et al, 2021; Kokaji et al, 2020), and the metabolomic and proteomic data were newly obtained in this study (Materials and Methods). We selected 28 metabolites, 15 enzymes, and 17 transcripts relevant to glucose metabolism from the metabolomic, proteomic, and transcriptomic data, respectively (Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…Liver-specific knockdown of CREB reduced fasting plasma glucose concentrations in ob / ob mice through downregulation of G6pc and Fbp1 (Erion et al, 2009). In addition to these key transcription factors identified by individual experiments, high-throughput measurements and multi-omic analyses have revealed many more transcription factors involved in metabolic alteration associated with obesity (Egami et al, 2021; Kokaji et al, 2020; Soltis et al, 2017). Although transcription factors contribute changes in metabolic flux in glucose metabolism associated with obesity, metabolic flux is also regulated by metabolites that include substrates, products, cofactors, and allosteric effectors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation